ANALISIS RASIO LIKUIDITAS, RASIO PROFITABILITAS, DAN RASIO SOLVABILITAS UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN PADA PT. SURYA TOTO INDONESIA TBK PERIODE 2010-2018 - Agustine, Clarissa (Perhimpunan Sarjana Ekonomi dan Bisnis, 2021)
This study aims to analyze the financial performance of PT. Surya Toto Indonesia Tbk when measured using a liquidity ratio in terms of CR, QR, and Cash Ratio. To analyze financial performance at PT Surya Indonesia when measured using profitability ratios in terms of ROA, MPM, ROE. To analyze financial performance at PT Surya Indonesia Tbk when measured using the solvency ratio in terms of DER, DAE, LTDtER. This research method using quantitative descriptive method. The data analysis technique uses the calculation of liquidity ratios, profitability ratios, and solvency ratios which refer to the Decree of the Minister of Finance of the Republic of Indonesia No. 740 / KMK.00 / 1989. Financial performance can be presented through a financial report for a period, because with financial reports an analysis can be done. The data used in this study are in the form of financial statements of PT. Surya Toto Indonesia Tbk, which consists of a balance sheet and profit and loss statement for the years 2010-2018. The results of the research analysis of financial ratios on the financial performance of PT Surya Toto Indonesia Tbk for the period 2010-2018 in terms of the liquidity ratio showed an average figure of 130.98% and can be said to be unhealthy. Then, in terms of the profitability ratio, it shows an average figure of 16.39% and it can be said to be unhealthy. And when viewed from the solvency ratio, it shows an average number of 45.06 and can be said to be very healthy